Spain and Don Ernesto. History of mutual love - A. Sudakova (Ибероамериканские тетради, 2019)
Bullfighting and wars, sun and waves, inevitable danger and careless rest make an inconsistent picture of Spain, which appears before us due to Ernest Hemingway’s labour. He was fond of this country, we shall try to understand, what for?